Peptoid drug discovery and optimization via surface X‐ray scattering. Issue 6 (20th March 2019) - Andreev, Konstantin; Martynowycz, Michael W.; Gidalevitz, David
Abstract: Synthetic polymers mimicking antimicrobial peptides have drawn considerable interest as potential therapeutics. N ‐substituted glycines, or peptoids, are recognized by their in vivo stability and ease of synthesis. Peptoids are thought to act primarily on the negatively charged lipids that are abundant in bacterial cell membranes. A mechanistic understanding of lipid–peptoid interaction at the molecular level will provide insights for rational design and optimization of peptoids. Here, we highlight recent studies that utilize synchrotron liquid surface X‐ray scattering to characterize the underlying peptoid interactions with bacterial and eukaryotic membranes. Cellular membranes are highly complex, and difficult to characterize at the molecular level. Model systems including Langmuir monolayers, are used in these studies to reduce system complexity. The general workflow of these systems and the corresponding data analysis techniques are presented alongside recent findings. These studies investigate the role of peptoid physicochemical characteristics on membrane activity. Specifically, the roles of cationic charge, conformational constraint via macrocyclization, and hydrophobicity are shown to correlate their membrane interactions to biological activities in vitro . These structure–activity relationships have led to new insights into the mechanism of action by peptoid antimicrobials, and suggest optimization strategies for future therapeutics based on peptoids. Abstract :